2020
DOI: 10.21577/0103-5053.20190250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Capping Agent PVP of the Outer Layer of Pd Nanocubes Surface on the Catalytic Hydrogenation of Unsaturated C−C Bonds

Abstract: The excess of capping agents used during the synthesis of nanoparticles is usually removed by solvent washing. The influence of the amount of polyvinylpyrrolidone (PVP) capping agent in the catalytic activity of palladium nanocubes was evaluated, after different numbers of washing cycles in the purification step performed after the syntheses of the nanoparticles. The effect of PVP amount on the hydrogenation of unsaturated carbon-carbon bonds was evaluated in terms of kinetic analysis and diffusion experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…[46a] ruled out when comparing their catalytic activities. [51] Similar structure analysis can be found for ZnO, [52] ZrO 2 , [53] WO 3 , [54] Pd, [55] Pt, [21b,56] and Au [57] nanoparticles.…”
Section: Bare Nanoparticlessupporting
confidence: 70%
See 1 more Smart Citation
“…[46a] ruled out when comparing their catalytic activities. [51] Similar structure analysis can be found for ZnO, [52] ZrO 2 , [53] WO 3 , [54] Pd, [55] Pt, [21b,56] and Au [57] nanoparticles.…”
Section: Bare Nanoparticlessupporting
confidence: 70%
“…analysed the influence of the PVP capping agent used for protecting Pd NPs on the hydrogenation of unsaturated carbon‐carbon bonds. Given that the X‐Ray scattering parameters agreed with Transmission Electron Microscopy (TEM) observations, they concluded that the NPs mean size were not affected by the purification procedure, and could be ruled out when comparing their catalytic activities [51] . Similar structure analysis can be found for ZnO, [52] ZrO 2 , [53] WO 3 , [54] Pd, [55] Pt, [21b,56] and Au [57] nanoparticles.…”
Section: Discussion Of Recent Literaturesupporting
confidence: 52%
“…The catalytic performance is influenced by the chemical nature of the stabilizer 25 and the respective degree of coating (how densely the metallic nanoparticles are coated by the polymer chains). 26 The key influence of the polymer capping was also evidenced by us with regard to biological properties. 21 The antimicrobial effect of AgNPs seems to be suppressed depending on the synthetic route and chemical nature of the capping agent used in their manufacturing.…”
Section: ■ Introductionmentioning
confidence: 73%
“…The organic shell might, nevertheless, influence the applicability of the produced colloidal material since the capping agent is able to influence antimicrobial properties and catalytic activity. , From the catalytic point of view, the adverse impact of capping agents is a consensus because it hampers the access of the reactants to the catalyst surface, , although their presence is inevitable to promote colloidal stability. The catalytic performance is influenced by the chemical nature of the stabilizer and the respective degree of coating (how densely the metallic nanoparticles are coated by the polymer chains) . The key influence of the polymer capping was also evidenced by us with regard to biological properties .…”
Section: Introductionmentioning
confidence: 86%
“…[39][40][41] Moreover, PVP increases the nanoparticle stability and reactivity of nanoparticles. 42,43 Aslan et al also reported that PVP could be used as a binding agent to bind the active materials into the current collector for supercapacitor applications. 44 However, PVP's role in enhancing the electrochemical properties has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%